MORPHOLOGY, PHYSIOLOGY AND MOLECULAR CHARACTERISTICS OF OIL PALM (Elaeis guineensis Jacq.) ENDOPHYTIC Bacillus sp. - Puspita, Fifi; Hadiwiyono, Hadiwiyono; Poromarto, Susilo Hambeg; Roslim, Dewi Indriyani (International Journal of Biosciences and Biotechnology, 2017)
Endophytic bacteria are the bacteria that live in plant tissues. In oil palm tissue there are many types of endophytic bacteria and have a role that can be beneficial for the plant, one of them is endophytic Bacillus sp. The aim of these research was to obtain morphology, physiology and molecular characteristics of endophytic Bacillus sp. originating from oil palm tissue. Sampling was done by random simple sampling method. Isolation of bacteria was performed on plant tissues such as roots, midribs, stems and leaves of oil palm plants. The results of morphological characterization such as colony color, colony shape and colony edge show similarity in each isolate but there are differences in the surface morphology of the colony, where there are 6 isolates with convex surface and 6 isolates with flat shape. Physiological test results such as catalase test, oxidase test, starch hydrolysis test, motility test and temperature effect test on bacterial growth showed positive results in each isolate. Molecular characterization using 16S rRNA primers based on BLASTn shows that all isolates tested have similarities with Bacillus sp. Based on the phylogenetic tree it was found that the endophytic bacteria of Ba-B2 isolates were associated with Bacillus flexus with 100% consistency index grouped at a distance of 0.03 and Ba-P2 isolates were related to Bacillus substilis at a distance of 0.01 with an 89% consistency index.